Felicia Hemans’s ‘The coronation of Inez de Castro’ (1830): feminine romanticism and the memorialisation of woman - Guimarães, Paula Alexandra (2013)
As Martin Nozick states, “There are certain characters in literature which exercise a perennial and self-renewing fascination on the creative mind” (1951: 330); although originated in different countries, they seem to belong to world literature. The inherent dramatic interest of the Inez de Castro’s story, in particular its romantic, idealistic qualities, and the pity, admiration and horror it arouses, has fascinated countless authors, calling not only for epic treatment (namely, in Camoes’s Lusiads) but also for a lyric one. The late Romantic woman poet Felicia Dorothea Browne Hemans (1793-1835) has been one of the first female authors to appropriate this European myth of love beyond death in her poem “The Coronation of Inez De Castro”, inserted in her volume Songs of the Affections (1830). After translating Camoes’s epic in 1818, and in the recent context of the Peninsular wars, Hemans became not only interested in Portuguese literature but also and, in particular, in the haunting theme of Inez de Castro’s fate. In fact, by 1825, Hemans had established herself as a popular poet by writing in part for an expanding market in medievalist literature, while also developing a feminine revisionist poetics. She radically transformed the historical material she absorbed, reconfiguring it according to a new domesticated, gendered and bourgeois class perspective. Critics of Felicia Hemans often discuss her historiography, observing that her poetry injects the domestic, the feminine and the sentimental into ‘official’ history. This paper suggests that Hemans’s ‘cosmopolitan’ historiography was rather a manifestation of a widespread Romantic-era conviction that history was not merely something to read about, but also an experience to be felt and a place to be visited. The poet’s exotic cultural displacement may seem romantically distancing and ‘derealising’, but its fictionality allows disturbingly familiar themes to emerge in a foreign scene that signals a universal condition. In its engagement with ‘the dead’ and its concomitant interest in imaginative historical transport, Hemans’s poem highlights tensions between ideals of affective proximity and critical distance, exposing the methodological difficulties of memorialisation. Centred on the events after Inez’s death, the poem is also intended as a Gothic ‘Tableau’ or ekphrasis of the unusual historical ceremony; the tragic figure of Inez is herself depicted as an uncanny sculpture or statue in flesh, thus further aestheticising and perpetuating the moment and its rich rituals. In the end, although Love is proclaimed as “mightier than Death”, there is an inescapable sense of “wasted worth” in the rewriting of woman’s history.